ANALISIS PENGGUNAAN GOOGLE MEET BERBASIS ANDROID MOBILE DALAM MINAT BELAJAR MAHASISWA INFORMATIKA - Rizki Noor Prasetyono (Informatika Publisher, 2020)
The purpose of this research is to find out how the impact of online learning using Google Meet based on Android Mobile on the learning interest of informatics students. This research uses quantitative descriptive by describing the data on student interest and response during learning using Google Meet based on Android Mobile and the results of the analysis using linear regression analysis to make conclusions. Research Results The use of Google Meet based on Android Mobile has an impact on learning interest in conditions of online learning. Then the percentage of influence on the use of Google Meet based on Android Mobile in interest in learning is 51.9%. The response also showed a percentage of 71% had good criteria to receive as learning during the pandemic.